2012
DOI: 10.1021/ja302367s
|View full text |Cite
|
Sign up to set email alerts
|

Click-Functionalized Compact Quantum Dots Protected by Multidentate-Imidazole Ligands: Conjugation-Ready Nanotags for Living-Virus Labeling and Imaging

Abstract: We synthesized a new class of mutifunctional multidentate-imidazole polymer ligands by one-step reaction to produce conjugation-ready QDs with great stability and compact size. Furthermore, combined with strain-promoted click chemistry, we developed a general strategy for efficient labeling of living-viruses with QD probes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
131
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(134 citation statements)
references
References 41 publications
3
131
0
Order By: Relevance
“…Liu and co-workers used a polyhistidine-and azide-modified block copolymer, starting from polymaleic anhydride, to cap luminescent QDs. 145 They showed that following ligand exchange the azide groups were accessible for further conjugation to the Baculovirus pre-modified with cyclooctyne through metal-free ''Click'' reaction. These conjugates were tested in the intracellular uptake by the A549 cell line.…”
Section: Bioconjugation To Target Moleculesmentioning
confidence: 99%
“…Liu and co-workers used a polyhistidine-and azide-modified block copolymer, starting from polymaleic anhydride, to cap luminescent QDs. 145 They showed that following ligand exchange the azide groups were accessible for further conjugation to the Baculovirus pre-modified with cyclooctyne through metal-free ''Click'' reaction. These conjugates were tested in the intracellular uptake by the A549 cell line.…”
Section: Bioconjugation To Target Moleculesmentioning
confidence: 99%
“…However, in these experiments, no CLEM was performed. Zhang et al [38] recently used a similar approach to image the intracellular presence of viruses. CdSe/ZnS Qdots were modified with an azide-containing outer coating.…”
Section: Bioorthogonal Labelling For Clem Imagingmentioning
confidence: 99%
“…The QDs are usually embedded in the matrixes to avoid their agglomeration, and in turn, the diverse structures of matrixes could widen the applications of QDs [4][5][6]. Polymers are most employed as matrixes for embedding the QDs due to their diversity, easy handing, and mechanical and chemical stability [6][7][8].…”
Section: Introductionmentioning
confidence: 99%